A Review on Electric Wheelchair Innovation to Ease Mobility and As a Rehabilitation Tool for Spinal Cord Impairment Patient - M. H., Muhammad Sidik; S. A., Che Ghani; M., Ishak; W. S., Wan Harun; N., Daud (IJET, 2020)
Wheelchair is used to assist disability people to do daily activities in order to reduce depending on other to continue their living. Adding some device into it, wheelchair can be not only help in mobilization, it can be rehabilitation device to the user. This review paper focus modifications done onto market available wheelchair. Variety types of sensor used to improve the mobility of electric wheelchair and to make it as a rehabilitation tools at the same time.